Enquête sur les conditions de travail auprès de professeurs d’éducation physique et sportive et perspectives d’action - Fabien Coutarel; Céline Mardon; Serge Volkoff; Jacques Fiard; Michel Récopé; Joffrey Beaujouan; Géraldine Rix (Perspectives Interdisciplinaires sur le Travail et la Santé)
Numerous studies in didactics and pedagogy have focused on the relation between the student and knowledge in their examination of how physical education and sports (PES) is taught in French colleges and high schools. In these studies, the only aspect of the teaching activity that is generally examined is how the teacher goes about building this student-knowledge relation. Many of the elements that are part of the teaching activity are consequently ignored, despite the fact that these elements appear to strongly contribute to the links built between the teacher, his work, and his students. Accordingly, the survey presented here aims to objectify the relation of PES teachers to their work, particularly through the relation between health effects, perception of work, and work conditions. Conducted in the Auvergne region of France with 218 PES teachers, the results showed that there was a gap between the positive general discourse about work and the specific answers to precise questions about the organization of work, the work collective, and health, these answers revealing real difficulties. A significant correlation appeared between certain difficulties regarding issues of work organization, workload, and the meaning of work on the one hand, and situations of fatigue and exhaustion on the other. Differences related to age and sex were moreover identified. Given that the highlighted difficulties can be addressed by an ergonomics approach, several possible associated actions can be considered: managing end-of-career transitions, developing work collectives and work organizations, conducting ergonomic intervention in teaching organizations and in the early phases of the design project, and taking teachers’ needs into account in their training.